2011
DOI: 10.1007/s00417-011-1731-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of therapy with mycophenolate mofetil in chronic non-infectious uveitis

Abstract: Our data show that mycophenolate mofetil is generally effective and well tolerated in the treatment of chronic non-infectious uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
2
17
3
1
Order By: Relevance
“…The average MMF dose in our study was 2.25 g/day (range 1-3 g/d), similar to other studies (20,22,24) . Most of the side effects in our series were observed with a dose of 3 g per day (three out of four patients).…”
Section: Side Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…The average MMF dose in our study was 2.25 g/day (range 1-3 g/d), similar to other studies (20,22,24) . Most of the side effects in our series were observed with a dose of 3 g per day (three out of four patients).…”
Section: Side Effectssupporting
confidence: 90%
“…This patient had favorable outcome after appropriate antibiotic therapy. inflammation with a prednisone dose of ≤10 mg per day after 1 or 2 years of MMF treatment (22) . Teoh found an 85% probability of reducing prednisone to ≤10 mg per day after one year of treatment (23) .…”
Section: Side Effectsmentioning
confidence: 99%
“…42 Despite its limited experiences in practice of uveitis, this drug has gained considerable popularity, reflected by the emerging publications on its effectiveness in this particular field, 44,[97][98][99][100][101][102][103] as well as its second priority among uveitis specialists' current choices of immunosuppressive drugs in the United…”
Section: Mmfmentioning
confidence: 99%
“…MMF use in ocular inflammation was first explored in animal models of experimental autoimmune uveoretinitis (Chanaud et al 1995), leading to a number of studies supporting its use in refractory human inflammatory eye diseases, including noninfectious uveitis and scleritis (Kilmartin et al 1998b;Larkin and Lightman 1999;Sen et al 2003;Greiner et al 2002;Lau et al 2003;Baltatzis et al 2003;Siepman et al 2006;Thorne et al 2005;Teoh et al 2008). Doycheva and colleagues conducted a retrospective case series of 60 uveitis patients treated with MMF for at least 5 years and found that control of inflammation was achieved in 72% of patients after 1 year of treatment and in 82% after 2 years (Doycheva et al 2011). Rates of long-term side effects were similar to those reported in studies of short-term use (Siepman et al 2006;Thorne et al 2005).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Side effects associated with MMF most commonly include gastrointestinal upset, malaise, fatigue, headaches, and infection (Jabs et al 2000;Doycheva et al 2011). Bone marrow suppression and liver toxicities are less common but routine laboratory monitoring is essential and patients should limit alcohol consumption (Jabs et Knickelbein et al 2015).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%